Optical Properties of Spin-Coated TiO2 Antireflection Films on Textured Single-Crystalline Silicon Substrates - Ryosuke Watanabe; Yohei Eguchi; Takuya Yamada; Yoji Saito (International Journal of Photoenergy)
Antireflection coating (ARC) prepared by a wet process is beneficial for low cost fabrication of photovoltaic cells. In this study, we investigated optical properties and morphologies of spin-coated TiO2 ARCs on alkaline textured single-crystalline silicon wafers. Reflectance spectra of the spin-coated ARCs on alkaline textured silicon wafers exhibit no interferences and low reflectance values in the entire visible range. We modeled the structures of the spin-coated films for ray tracing numerical calculation and compared numerically calculated reflectance spectra with the experimental results. This is the first report to clarify the novel optical properties experimentally and theoretically. Optical properties of the spin-coated ARCs without interference are due to the fractional nonuniformity of the thickness of the spin-coated ARCs that cancels out the interference of the incident light.